PHILOSOPHICAL DOCTRINE OF KANT AS FINDING AUTHENTICAL FORMS OF ANTROPOLOGICAL METAPHYSICAL ФИЛОСОФСКОЕ УЧЕНИЕ КАНТА КАК ПОИСКИ АУТЕНТИЧНОЙ ФОРМЫ АНТРОПОЛОГИЧЕСКОЙ МЕТАФИЗИКИ ФІЛОСОФСЬКЕ ВЧЕННЯ КАНТА ЯК ПОШУКИ АВТЕНТИЧНОЇ ФОРМИ АНТРОПОЛОГІЧНОЇ МЕТАФІЗИКИ - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Виходячи з запитаності в сучасній культурі метафізичного осмислення природи людини, укоріненого в філософському спадку Канта, автор зосереджує увагу на експлікації
антропологічних інтенцій кантівських «Критик», акцентуючи амбівалентність позиції мислителя на проблемі автентичної форми метафізичної антропології. Contemporary culture needs metaphysical understanding of human nature based on the philosophical heritage of Kant. According to this assertion the author gives heed to explication of
Kant's famous anthropological intention of his "critiques". The author focuses attention on the ambivalent attitude of the philosopher on the issue of authenticity of metaphysical anthropology. Учитывая насущную необходимость в современной культуре метафизического осмысление природы человека, укорененного в философском наследии Канта, автор сосредотачивает внимание на экспликации антропологической интенции знаменитых кантовских «Критик», акцентируя амбивалентность позиции философа на проблеме аутентичности метафизической атропологии.